Endometritis as a result of a foreign body reaction to an anti-adhesive barrier: a report of two cases - Chin-Jung Wang; Cindy Hsuan Weng; Kai-Yun Wu; Yu-Shan Lin; An-Shine Chao (IMR Press, 2022)
Background: We present two patients who suffered from endometritis as a result of a foreign body reaction to an anti-adhesive barrier positioned during hysteroscopic surgery. Case: The first case-who had previously undergone hysteroscopic lysis of intrauterine adhesions-presented with persistent abdominal pain and vaginal discharge. Ultrasound revealed an irregularly shaped strip of hyperechoic lesion. On diagnostic hysteroscopy, a foreign body presenting as a flattened bundle was observed and identified as the anti-adhesive barrier positioned during her previous surgery. The second patient-who had previously undergone laparoscopic surgery and hysteroscopic polypectomy-presented with abdominal pain in the left lower quadrant. Ultrasound revealed an intrauterine hyperechoic avascular lesion, while hysteroscopy identified a piece of crumpled plastic wrap. Both patients showed clinical improvement after removal of the extraneous material. Conclusion: Intrauterine positioning of anti-adhesive barriers during hysteroscopic surgery can give rise to endometritis as a result of foreign body reactions.